High Moment and Pathwise Error Estimates for Fully Discrete Mixed Finite Element Approximations of Stochastic Navier-Stokes Equations with Additive Noise (Communications in Computational Physics, 2024)
This paper is concerned with high moment and pathwise error estimates forfully discrete mixed finite element approximations of stochastic Navier-Stokes equations with general additive noise. The implicit Euler-Maruyama scheme and standardmixed finite element methods are employed respectively for the time and space discretizations. High moment error estimates for both velocity and time-averaged pressure approximations in strong $L^2$ and energy norms are obtained, pathwise error estimates are derived by using the Kolmogorov Theorem. Unlike their deterministiccounterparts, the spatial error constants grow in the order of $\mathcal{O}(k^{-\frac{1}{2}} ),$ where $k$ denotestime step size. Numerical experiments are also provided to validate the error estimatesand their sharpness.
Keywords: Stochastic Navier-Stokes equations; additive noise; Wiener process; Itô stochastic integral; mixed finite element methods; inf-sup condition; high moment; and pathwise error estimates.